Around the World on a Bicycle: A Study of American Manhood 1884-1887 - Rau, Jeremiah (My University, 2014)
In 1886 Thomas Stevens became the first man to circle the globe on a bicycle. The feat was an amazing accomplishment for the time but his account is far more than just an interesting anecdote in history; his overall journey and press coverage highlight a popular ideals of American manhood in the late 1880s. At the time, manhood in general was an exclusive condition; it was specific to white middle class men and needed to be proven either in the burgeoning marketplace and/or by strenuous acts of adventure. Bicycling in the early 1880s was an activity for young, wealthy, white men. This paper shows how Steven?s decision to bicycle around the world was, in part, due to popular conceptions of American manhood and how the "manly" culture surrounding the bicycle in the United States during the 1880s became a means through which Stevens could achieve normative manhood. Although we cannot be sure what Stevens thought to himself, his decision to bicycle around the globe was not only a means to make a living--he could achieve that through more ordinary means, it was a way to achieve his own manhood in a culture which valued toughness, passion, and freedom as male virtues.
Keywords: Stevens, Thomas, 1854-1935; Cycling--History--19th century; Masculinity--United States--History--19th century; Voyages around the world--History--19th century